MODERN APPROACHES TO LABORATORY EVALUATION OF ANEMIAS OF VARIOUS ETIOLOGIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Anemias of various etiologies represent one of the most common hematological problems in clinical practice and are associated with a significant reduction in patients’ quality of life. The diversity of etiological factors and pathogenetic mechanisms underlying anemia necessitates the use of a comprehensive and differentiated laboratory approach to diagnosis. This article reviews modern laboratory methods for the diagnosis of anemia based on the assessment of complete blood count parameters, erythrocyte morphology, indicators of iron metabolism, vitamin B₁₂ and folic acid levels, as well as markers of hemolysis and inflammation. Particular attention is paid to the differential diagnosis of iron deficiency anemia, megaloblastic anemia, hemolytic anemia, and anemia of chronic disease. The application of modern laboratory technologies improves diagnostic accuracy, enables timely determination of anemia etiology, and optimizes therapeutic strategies.